Synthetic Design and Biological Evaluation of New p53-MDM2 Interaction Inhibitors Based on Imidazoline Core - Daniil R. Bazanov; Nikolay V. Pervushin; Egor V. Savin; Michael D. Tsymliakov; Anita I. Maksutova; Victoria Yu. Savitskaya; Sergey E. Sosonyuk; Yulia A. Gracheva; Michael Yu. Seliverstov; Natalia A. Lozinskaya; Gelina S. Kopeina (MDPI AG, 2022)
The use of p53-MDM2 inhibitors is a prospective strategy in anti-cancer therapy for tumors expressing wild type p53 protein. In this study, we have applied a simple approach of two-step synthesis of imidazoline-based alkoxyaryl compounds, which are able to efficiently inhibit p53-MDM2 protein-protein interactions, promote accumulation of p53 and p53-inducible proteins in various cancer cell lines. Compounds 2l and 2k cause significant upregulation of p53 and p53-inducible proteins in five human cancer cell lines, one of which possesses overexpression of MDM2.